Distinct changes in evoked and resting globus pallidus activity in early and late Parkinson's disease experimental models - Zold, Camila Lidia (2007)
The main clinical manifestations of Parkinson´s disease are caused by alterations of basal ganglia activity that are tied in with the progressive loss of mesencephalic dopaminergic neurons. Recent theoretical and modeling studies have suggested that changes in resting neuronal activity occurred later in the course of the disease than those evoked by phasic cortical input. However, there is no empirical support for this proposal. Here we report a marked increase in the responsiveness of globus pallidus neurons to electrical motor cortex stimulation, in the absence of noticeable changes in resting activity, in anesthetized rats that had consistently shown a deficit in forelimb use during behavioral testing before the experiments, and had approximately 45% dopamine neurons spared in the substantia nigra. Pallidal neurons were also over-responsive to motor cortex stimulation and lost spatial selectivity for cortical inputs in rats with extensive nigrostriatal damage. After partial lesions, over-responsiveness was mainly due to an increased proportion of neurons showing excitatory responses, while extensive lesions led to an increased likelihood of inhibitory responding neurons. Changes in resting neuronal activity, comprising pauses disrupting tonic discharge, occurred across different global brain states, including an activated condition which shares similarities with natural patterns of cortical activity seen in awake states and rapid eye-movement sleep, but only after massive nigrostriatal degeneration. These results suggest that a loss of functional segregation and an abnormal temporal encoding of phasic cortical inputs by globus pallidus neurons may contribute to inducing early motor impairment in Parkinson´s disease.